Red Seal Landscape Horticulturist Identify Plants and Plant Requirements - Nakano, Michelle; Open Textbook Library (Open Textbook Library, 2020)
Red Seal Landscape Horticulturist Identify Plants and Plant Requirements is an adaptation of KPU HORT 1155 Introduction to Plant Materials Lecture Notes. It is an editable, open access learning resource with interactive web based experiences customized for horticulture students studying plant identification. This first edition supports student achievement of the Level 1 and 2 learning goals for Red Seal Landscape Horticulturist Line F2: Identify plant and plant requirements for a range of plants commonly used in horticulture Employ correct naming and plant identification terminology Identify morphological characteristics, growing requirements, use and availability Use a dichotomous key for plant identification Explain plant hardiness Identify weedy and invasive plants
Part 1 - Plant Identification -- 1. Introduction to Plant -- 2. Introduction to Taxonomy -- 3. Introduction to Taxons -- 4. Introduction to Binomial Nomenclature -- 5. Conventions for Binomial Nomenclature -- 6. Nomenclature Review -- 7. The Meaning of Plant Names -- 8. Plant Growth -- 9. Introduction to Plant Classification -- 10. Classify Plants by Life Cycle -- 11. Introduction to Dichotomous Keys -- 12. Key to Plant Classification -- 13. Introduction to Plant Morphology -- 14. Plant Morphology - Leaves -- 15. Plant Morphology - Conifers -- 16. Plant Morphology - Flowers and Fruit -- 17. Plant Family Characteristics -- Part 2 Plant Requirements and Use -- 18. Plant Habitats -- 19. Plant Use Categories -- 20. Plant Growth Characteristics -- 21. Characteristics of weedy species -- 22. Plant Hardiness -- 23. Plant Requirements
In English.
Description based on print resource
Keywords: Earth Sciences -- Textbooks; Science -- Textbooks